Episiotomy and severe perineal laceration among Asian American, Native Hawaiian, and Pacific Islander nulliparous individuals in CaliforniaAJOG Global Reports at a Glance - Tracy Chidyausiku, MS; Shalmali Bane, PhD; Meryl M. Sperling, MD; Elliott K. Main, MD; Suzan L. Carmichael, PhD (AJOG Global Reports)
Background: Asian American, Native Hawaiian, and Pacific Islander individuals have increased risks for episiotomy and severe perineal laceration during vaginal delivery. The Asian American, Native Hawaiian, and Pacific Islander population in the US is diverse yet few studies disaggregate results within specific ethnicity populations. Objective: This study investigated the variability in risks for episiotomy and severe perineal laceration among 16 disaggregated Asian American, Native Hawaiian, and Pacific Islander groups, compared to Non-Hispanic White nulliparous individuals, and assessed what factors may explain the variability in risk. Study design: Birth and fetal death certificate files linked to hospital discharge records were used to identify nulliparous, term, singleton, vertex vaginal deliveries among California births, 2007 to 2020. Poisson regression models were used to examine risks of episiotomy and severe perineal laceration among 16 Asian American, Native Hawaiian, and Pacific Islander ethnicity subgroups compared with Non-Hispanic White individuals. Sequential adjustment was utilized to assess if maternal social, health-related, and delivery-related factors may explain the variability in risk for episiotomy and severe perineal laceration. Results: Among the 224,964 Asian American, Native Hawaiian, and Pacific Islander individuals in this study cohort, the overall prevalence of episiotomy was 18.5% (N = 41,559) and prevalence of severe perineal laceration was 8.9% (N = 20,013); the prevalence of both outcomes declined during the study period. Within subgroups, prevalence of episiotomy ranged from 9.8% among Other-Pacific Islander individuals to 24.5% among Korean individuals. Prevalence of severe perineal laceration ranged from 3.4% in Guamanian individuals to 15.2% in Indian individuals. In fully adjusted models, risk ratios were greater than 1.0 (with confidence intervals excluding 1.0) for 6 subgroups for episiotomy and 9 subgroups for severe perineal laceration, compared to Non-Hispanic White individuals. After adjustment, Korean individuals were at highest risk of episiotomy (adjusted risk ratio 1.80 [95% CI 1.75, 1.85]), and Indian individuals were at highest risk of severe perineal laceration (adjusted risk ratio 2.14 [95% CI 2.07, 2.21]). Adjustment for social factors (nativity; education; payer) tended to attenuate risk ratios; subsequent adjustment for maternal health and delivery-related factors including maternal age, height, pre-pregnancy body mass index, hypertension, diabetes, gestational weight gain, fetal stress/incomplete fetal head rotation (occiput transverse or posterior), large infant size or shoulder dystocia, and forceps/vacuum did not impact risk ratios substantially. Conclusion: Prevalence and risks of episiotomy and severe perineal laceration varied widely among Asian American, Native Hawaiian, and Pacific Islander births in California from 2007 to 2020. The variability in risks was more influenced by differences in social rather than maternal health and delivery-related factors. This study adds to the growing understanding of disparities in health outcomes among Asian American, Native Hawaiian, and Pacific Islander subgroups.